Pengaruh Likuiditas, Profitabilitas Dan Ukuran Perusahaan Terhadap Nilai Perusahaan (Studi Kasus Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2024) - Fitria Permata; Elvi Rahmi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
The average value of companies in the Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange in 2019-2024 fluctuated. The data also shows that there are still companies that have a PBV value <1, while the standard PBV is 1. The purpose of this study is to determine the Effect of Liquidity, Profitability and Company Size on Company Value (Case Study of Food and Beverage Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange in 2019-2024). The type of research is quantitative. The population in this study is 95 Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange and a sample of 12 companies. The analysis method is multiple linear regression analysis. The results of the study indicate that there are (1) The influence of liquidity, profitability and company size has a significant effect on company value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange 2019-2024. (2) Liquidity has a negative and significant effect on company value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange 2019-2024. (3) Profitability has a negative and insignificant effect on company value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange 2019-2024 and (4) Company size has a negative and insignificant effect on company value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange 2019-2024.